Block chain for smart systems : computing technologies and applications - Malik, Latesh; Arora, Sandhya; Shrawankar, Urmila; Deshpande, Vivek (Boca Raton : Chapman & Hall\CRC Press, 2022)
"Blockchain technology has been penetrating every aspect of Information and Communications Technology (ICT) and its use has been growing rapidly in recent years. The interest and development of this technology has primarily been driven by the enormous value growth of cryptocurrencies and large investments of venture capital in blockchain start-ups. Block Chain for Smart Systems: Computing Technologies and Applications is intended to clarify and define in simple terms, the technology behind blockchain, a deep-dive into the core fundamentals of blockchain: hashing algorithm behind each block, distributed technology, smart contracts, private vs public blockchain. Features Discusses fundamental theories to practical and sophisticated applications of Blockchain technology Includes case studies Discusses the concepts with illustrations, appropriate figures, tables and simple language This book is primarily aimed at undergraduates, graduates, research scholars, academicians, industry and technology enthusiasts working in various aspects of block chain technology"--
Blockchain fundamentals / Sheetal Thakare, M A Pund -- Basics of blockchain architecture / Supriya Aras, Mangesh Bedekar -- Unblobking the blockchain : concepts and use cases / Padma Adane -- BlockCloud : blockchain as a cloud service / Urmila Shrawankar -- A deep dive into blockchain consensus algorithms / Nupur Kulkarni, Rohini Pise, Sonali Patil -- Blockchain computing technology : challenging security and privacy issues / Sonali Nimbhorkar -- Decentralization in blockchain and its impact on identity management system / Shailaja Lohar, Sachin Babar -- Threat to the current blockchain cryptosystems due to the advancement of quantum computers / Maulik Pandya -- Digital india digital economy using blockchain technology / Kalpana Thakre, Gargi Kulkarni, Prajwal Deshmukh -- Blockchain based secure evidence management police assistance system / Rohini Pise, Sonali Patil -- Blockchain for healthcare systems / Shreeya Patil -- Smart microgrid based energy management using blockchain / Rashmi Jain, Sachin Jain, Sanchit Jain.
OCLC-licensed vendor bibliographic record.
Keywords: Blockchains (Databases); COMPUTERS / Machine Theory; COMPUTERS / Artificial Intelligence